[NH2CHNH2]3Sb2I9: a lead-free and low-toxicity organic–inorganic hybrid ferroelectric based on antimony(iii) as a potential semiconducting absorber. Issue 8 (30th March 2020) - Szklarz, Przemysław; Jakubas, Ryszard; Gągor, Anna; Bator, Grażyna; Cichos, Jakub; Karbowiak, Mirosław
Abstract : A novel room-temperature ferroelectric crystal with the complex sequence of phase transitions. Abstract : We report the physicochemical characteristics of a novel Sb-based formamidinium ferroelectric material, (NH2 CHNH2 )3 Sb2 I9 (FAIA ). FAIA crystallizes at room temperature in the hexagonal P 63 mc space group. The crystal structure of FAIA is isomorphic to that of its bismuth analog, [NH2 CHNH2 ]3 Bi2 I9 (FAIB), which is characterized by a zero dimensional (0D) anionic network (discrete bioctahedral units). From the DSC results three phase transitions (PT) have been found for FAIA : at 187.4/189 K (phase I ↔ phase II ), 177.6/177.9 K (II ↔ III ) and 148.2/152.3 K (III ↔ IV ). The compound exhibits ferroelectricity in the room temperature phase I and in the successive temperature phases (II and III) . The spontaneous polarization ( P S = 0.5 × 10 −2 μC cm −2 ) reversibility has been confirmed by the presence of the ferroelectric hysteresis loops and pyroelectric measurements. The origin of ferroelectricity is discussed in terms of the cationic dynamics. This material may be considered as a semiconductor ( σ ∼ 10 −6 S m −1, 300 K).